Koli man venturing out for fishing - Mumbai Archive Project Team (Jio Institute, 2024)
Historical records suggest that the Kolis have inhabited the Mumbai coastline for hundreds, if not thousands, of years. Living in hamlets scattered along the coastline, they earn their living primarily through fishing, trading, and other maritime activities, although some Kolis also engage in farming.